Preparation and characterization of syrup from native dried date (Phoenix dactylifera L., variety Mech-Degla) fruits (Indian Journal of Traditional Knowledge (IJTK), 2023)
Presently, three different evaporation procedures (oven heating, rotary evaporator, and lyophilization) were investigated at laboratory scale, for obtaining date (Phoenix dactylifera L.) syrup (DS) from date juice (DJ). The DJ was prepared by immersion of pitted date fruit (DF) pieces in pure water, according to the local traditional procedure. Compared to oven heating and lyophilization, the use of the rotavapor at 70°C seems to be more rational, since three hours of treatment are needed to reach a total of soluble solids (TSS) of about 61 Bx, against 6 and 18 h in the case of the two other cases, respectively. In addition, the DS thus obtained shows a lowest content in hydroxymethylfurfural (HMF). From the point of view of rheological behavior, the final DS is of pseudo-plastic (Bingham) type, comparable to white syrup taken here as reference. Considering the growing interest for natural products, the DS can advantageously replace commercial white syrups.